COVID-19, leprosy, and neutrophils. - Veronica Schmitz; Jéssica Brandão Dos Santos (Public Library of Science (PLoS), 2021)
Coronavirus Disease 2019 (COVID-19), a disease caused by the betacoronavirus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has only recently emerged, while Mycobacterium leprae, the etiological agent of leprosy, has endured for more than 2,000 years. As soon as the initial reports of COVID-19 became public, several entities, including the Brazilian Leprosy Society, warned about the possible impact of COVID-19 on leprosy patients. It has been verified that COVID-19 carriers can be either asymptomatic or present varying degrees of severe respiratory failure in association with cytokine storm and death, among other diseases. Severe COVID-19 patients show increased numbers of neutrophils and serum neutrophil extracellular trap (NET) markers, in addition to alterations in the neutrophil-to-lymphocyte ratio (NLR). The absence of antiviral drugs and the speed of COVID-19 transmission have had a major impact on public health systems worldwide, leading to the almost total collapse of many national and local healthcare services. Leprosy, an infectious neurological and dermatological illness, is widely considered to be the most frequent cause of physical disabilities globally. The chronic clinical course of the disease may be interrupted by acute inflammatory episodes, named leprosy reactions. These serious immunological complications, characterized by cytokine storms, are responsible for amplifying peripheral nerve damage. From 30% to 40% of all multibacillary leprosy (MB) patients experience erythema nodosum leprosum (ENL), a neutrophilic immune-mediated condition. ENL patients often present these same COVID-19-like symptoms, including high levels of serum NET markers, altered NLR, and neutrophilia. Moreover, the consequences of a M. leprae-SARS-CoV-2 coinfection have yet to be fully investigated. The goal of the present viewpoint is to describe some of the similarities that may be found between COVID-19 and leprosy disease in the context of neutrophilic biology.